Nutrition and biomass allocation of tomato (Solanum lycopersicum L.) plant influenced by mulching and organic fertilizers (Dhaka University Journal of Biological Sciences, 2025)
Global demand for vegetable crops has surged in this era of globalization and increased health awareness. Due to its rich nutritional and chemical composition, tomato (Solanum lycopersicum L.) has become one of the most popular and widely consumed vegetables worldwide. In response, a field experiment was conducted in net house at the Department of Soil, Water, and Environment, University of Dhaka, Bangladesh, to evaluate the effects of organic fertilizers, both alone and in combination with mulching, on the nutrient content and biomass allocation of tomato plants. The results indicated that the application of organic fertilizers such as mustard oil cake (MOC), poultry manure (PM), and vermicompost (V) at higher rates (8 t ha⁻¹) significantly increased the nutrient contents (N, P, K, S, Ca, and Mg) in the leaves, stems, and roots of tomato plants in absence of mulching. However, applying these fertilizers at lower rates (4 t ha⁻¹) in combination with mulching also effectively enhanced nutrient content. Regarding biomass allocation, particularly the root-to-shoot ratio, a slight anomaly was observed. The highest root-to-shoot ratio was recorded in the control plot, suggesting that factors other than nutrient supply, such as root penetration depth, distribution in the soil, response to transient drought, initial root growth and also environmental or physiological conditions, might have influenced root weight. Therefore, variations in root-to-shoot ratios could be misleading from a physiological perspective. To meet the growing demand for high-yielding, fertilizer-responsive crops, there has been significant reliance on synthetic inputs, raising concerns about the long-term sustainability of agricultural systems. Thus, environmentally friendly farming methods are urgently needed to ensure sustainable food production. The combination of mulching and organic fertilizers presents an effective strategy for improving crop growth conditions, increasing yield, and enhancing product quality by mitigating unfavorable environmental conditions.Dhaka Univ. J. Biol. Sci. 34(1): 25-40, 2025 (January)